Is there loss aversion in buying? An adversarial collaboration - Ian Bateman; Daniel Kahneman; Alistair Munro; Chris Starmer; Robert Sugden (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2003)
This paper reports an exercise in adversarial collaboration. An adversarial collaboration is an investigation carried out jointly by two individuals or research groups who, having proposed conflicting hypotheses, seek to resolve the issue in dispute. The experiment reported was designed to reconcile differences between the apparently conflicting results of two previous experiments, one carried out by Kahneman, the other by the other authors. Specifically, it investigates whether, when consumers consider giving up money in exchange for goods, they construe potential money outlays as losses. This issue bears on the explanation of the widely observed disparity between willingness-to-pay and willingness-to-accept valuations of costs and benefits, which has proved so problematic for contingent valuation studies. The results of the experiment do not decisively resolve the question in dispute, but they are broadly consistent with the hypothesis that money outlays are perceived as losses.
Keywords: 330; Adversarial collaboration; loss aversion; reference-dependent preferences; status quo bias; willingness to pay; Willingness to pay; Kooperation; Präferenztheorie; Nutzentheorie